Pengaruh Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Hasil Belajar IPAS Siswa Kelas V SDN 180 Bottobenteng Kabupaten Wajo - Sudarto, Sudarto; Muh. Idris Jafar; Saskia Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is an experimental study that aims to determine whether the use of the Two Stay Two Stray (TSTS) model has an effect or not on the learning outcome of IPAS in the 5th Grade students of SDN 180 Bottobenteng. The research design used is One-Group Pretest Postest Design. The population in this study were all of the 5th Grade students of SDN 180 Bottobenteng with a sample of 17 students selected based on the saturated sample technique. The data collection technique used was a test to determine the results of the students' learning outcome of IPAS before and after using the Two Stay Two Stray model. The data analysis used was descriptive and inferential statistical analysis. Results: from the descriptive statistical analysis, the average pretest was of 60.00 and the average posttest was of 80.5, from the inferential analysis using the paired sample t-test with a significance level of 5%, tcount (16.11)> ttable (2.12) was obtained, which means that H0 is rejected and H1 is accepted, which means that the students' IPAS learning outcomes before and after using the Two Stay Two Stray model are significantly different. Conclusion: because the average of the students' learning outcomes of IPAS after using the Two Stay Two Stray model (posttest) is higher than the average of students' IPAS learning outcomes before using the Two Stay Two Stray model (pretest) and is significantly different, it can be concluded that the Two Stay Two Stray model has an effect to improving the IPAS learning outcomes of the 5th Grade of SDN 180 Bottobenteng, Wajo Regency.